Host genetic factors that limit HIV and AIDS - Winkler, Cheryl A. (Henry Stewart Talks, 2013)
Overview of candidate gene association studies of HIV and AIDS, Key role for genetic variants involved in cell entry and host defenses, Homozygous CCR5 32 basepair deletion prevents HIV Infection, Acquired Immunity: HLA Class 1 proteins, Key mediators of HIV progression, Innate Protection: HLA and KIRS interactions in HIV disease, Overview of Genome Wide Association Studies (GWAS), Overwhelming influence of HLA class I on HIV Progression and control of HIV viral load, Non-HLA genetic associations with extreme phenotypes, No new variants identified that prevent HIV infection, Discovery of chromosome 22 associations with HIV-associated nephropathy, Future studies, Epigenetic, proteomic, functional studies, Potential role of rare variants